Propane-1,2-diaminium bis(pyridine-2,6-dicarboxylato-κ(3) O (2),N,O (6))cuprate(II) tetrahydrate - Aghabozorg, Hossein (International Union of Crystallography, 2011)
In the title compound, (C(3)H(12)N(2))[Cu(C(7)H(3)NO(4))(2)]·4H(2)O, the Cu(II) atom is six-coordinated in a distorted octahedral geometry by two tridentate pyridine-2,6-dicarboxylate (pydc) ligands. In the crystal, intermolecular O—H⋯O, N—H⋯O and weak C—H⋯O hydrogen bonds, as well as π–π stacking interactions between the pyridine rings of the pydc ligands [centroid–centroid distance = 3.4714 (14) Å] are present. C=O⋯π interactions between the carbonyl groups and pyridine rings [O⋯centroid distances = 3.150 (2) and 3.2233 (19) Å] are also observed.